Experience in Performing Bidirectional Cavopulmonary Anastomosis in the Surgical Treatment of Tricuspid Atresia - Ivan V. Dziuryi; Iaroslav P. Truba; Liliya M. Prokopovych; Vasyl V. Fylypchuk; Vasyl V. Lazoryshynets (Український журнал серцево-судинної хірургії, 2022)
Tricuspid atresia (TA) is a rare cyanotic congenital heart disease (CHD) first described by Kreysig (1817). Bidirectional cavopulmonary anastomosis (BCPA) is part of the hemodynamic correction of such a complex combined CHD. In patients after BCPA, blood flow through the superior vena cava, providing efficient pulmonary blood flow, is the most important factor influencing blood oxygen saturation.